Income effects of unemployment and short-time work in the East German transformation process - Johannes Schwarze; Ulrich Rendtel; Felix Büchel (Deutsches Institut für Wirtschaftsforschung (DIW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1993)
Income effects of unemployment and involuntary short-time work are investigated in the context of the East German transformation process from a planned socialistic economy to a market-oriented economy. Theoretical considerations from human capital theory are derived for the income effects in case of later employment. Special attention is given to the benefits of officially supported training courses and impacts of a change to a new firm. The estimation of income effects uses a variance components model which reflects not only a time-constant unobserved heterogenity but also person-related components which are linked to the two economic regimes. The empirical basis is the German Socio-economic Panel (GSOEP) which provides income and employment data for both periods.
Keywords: 330